2023
DOI: 10.1002/adma.202212065
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Assembly of Pleomorphic Bacterial Microcompartment Shell Architectures Spanning the Nano‐ to Microscale

Abstract: Many bacteria use protein-based organelles known as bacterial microcompartments (BMCs) to organize and sequester sequential enzymatic reactions. Regardless of their specialized metabolic function, all BMCs are delimited by a shell made of multiple structurally redundant, yet functionally diverse, hexameric (BMC-H), pseudohexameric/trimeric (BMC-T), or pentameric (BMC-P) shell protein paralogs. When expressed without their native cargo, shell proteins have been shown to self-assemble into 2D sheets, open-ended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In the context of engineering synthetic BMCs, the templating of shell proteins on coacervates and ATPS systems promises to allow the construction of larger shell systems-tens-of-micronscompared to the 20 nm to ≈1.8 μm range currently achieved so far. [26,108] Moreover, the ability to combine BMC shell proteins with LLPS systems points to the potential for developing micronscale synthetic BMC shells with distinct permeabilities, internal solvent properties, microenvironments, and pre-loaded cargos. Although under currently studied conditions, our selected BMC shell proteins may not completely cover a droplet's surface, incomplete coatings still may alter molecular diffusion and surface exchange as evidenced by cellular condensates stabilized by other interfacial protein clusters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of engineering synthetic BMCs, the templating of shell proteins on coacervates and ATPS systems promises to allow the construction of larger shell systems-tens-of-micronscompared to the 20 nm to ≈1.8 μm range currently achieved so far. [26,108] Moreover, the ability to combine BMC shell proteins with LLPS systems points to the potential for developing micronscale synthetic BMC shells with distinct permeabilities, internal solvent properties, microenvironments, and pre-loaded cargos. Although under currently studied conditions, our selected BMC shell proteins may not completely cover a droplet's surface, incomplete coatings still may alter molecular diffusion and surface exchange as evidenced by cellular condensates stabilized by other interfacial protein clusters.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] In general, empty synthetic compartments are typically ≈40 nm or less with a few exceptions. [26,27] Larger compartments (≈600 nm) have been produced by Bari et al [28] by templating BMC shell protein assembly around an aqueous-in-oil droplet. Additionally, theoretical and computational efforts suggest that interior cargos, along with a tile's intrinsic preference for a tile-tile curvature angle, influence the size, shape, and productive assembly of compartments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been found in simulations which assume shell proteins demonstrate no spontaneous curvature of their own [motivated by atomic force microscopy studies on shell subunits ( Sutter et al., 2016 ; Garcia-Alles et al., 2017 )] and can essentially trap a growing cargo droplet out of equilibrium ( Rotskoff and Geissler, 2018 ). This, however, may depend on the system of study as shell proteins have been observed to form sheets, nanotubes, and empty icosahedra among other morphologies, sometimes within the same sample ( Ferlez et al., 2023 ), without the need of cargo templating to induce curvature ( Ferlez et al., 2023 ; Trettel and Winkler, 2023 ; Uddin et al., 2018 ; Hagen AR. et al., 2018 ; Noël et al., 2015 ).…”
Section: Modeling the Physical Principles Underlying Carboxysome Asse...mentioning
confidence: 99%
“…63 A recent report suggests the formation of pleiotropic structures including nanotubes and nanocones when six shell proteins of a GRM from Rhodopseudomonas palustris were expressed in E. coli . 90 The self-assembly of shell proteins into such diverse types of structures disclosed the wide plasticity of BMC in bio-material applications.…”
Section: Engineering Bmc For Biomaterials Applicationsmentioning
confidence: 99%